The Influence of Number Dice Games in Improving Early Childhood Mathematical Logic in Early Childhood Education - Sari, Renta; Omeiza, Idris Ibrahim; Mwakifuna, Monica Asagwile (Interval: Indonesian Journal of Mathematical Education, 2023)
Purpose of the study: The aim of this research is to determine the effect of the number dice game in improving the mathematical logic intelligence of young children in Early Childhood Education. Methodology: The method used in this research is quantitative with an experimental research design, the sampling technique is purposive sampling, with post test and pre test research instruments, the data analysis used is inferential statistics. Main Findings: The results of this research show that Early Childhood Education Teachers use the number dice game media used in mathematics learning, which is a game that children like because it is very easy and interesting to play. In order to stimulate various areas of development such as cognitive, language and social. Social skills trained in this game include the willingness to follow and obey the rules of the game, playing in turns. Mathematical cognitive skills that are stimulated are stating the order of numbers, recognizing number symbols and number concepts. Novelty/Originality of this study: The use of a number dice game introduces a novel and engaging way for young children to interact with mathematical concepts. It offers an enjoyable learning experience that can potentially enhance children's motivation and interest in mathematics, establishing a positive foundation for learning.